Revitalizing Oral Literature Through Media Training and Time Storytelling for Parents and PAUD / Aisyiah Kindergarten Teachers in South Jakarta - Puspitasari, Nur Aini; Hidayatullah, Syarif; Jupri, Abdul Rahman (Universitas Nusantara PGRI Kediri, 2019)
Oral literature is rarely found in people's lives, especially in terms of storytelling. In fact, in fairy tales, there are values ​​of character education that can be instilled in children or students. For this reason, in an effort to revitalize the storytelling tradition, the team conducted media training and time to tell stories to parents and PAUD / TK Aisyiah teachers in Jakarta Selatan. To improve skills and awareness in storytelling, the team used training methods. In this method, the team gave lectures, discussions, and practices so that the participants were able to understand and apply the material that had been given. This activity was carried out at PAUD Aisyiah Petukangan Utara and TK Aisyiah 29 Jakarta Selatan. The material provided was the use of media in storytelling in the form of book and non-book media and storytelling time. The results of this training activity were that parents and teachers were able to practice storytelling with book and non-book media and understand the timing of storytelling well.